An experimental study on the closure of oroantral communications (OAC'S) with an injectable alloplastic material in rabbits - Amat, Shantelle Hazel S.
The occurrence of oroantral perforations is not uncommon due to the anatomical proximity of the roots of the maxillary posterior teeth to the sinus. Perforations smaller than 5 mm may close spontaneously but these, however, are hard to predict. Thus, oroantral communications (OAC's) should be surgically closed immediately. Conventionally, OAC's are closed using either buccal pedicle flaps or palatal pedicle flaps. There are also other several techniques employed to close OAC's: use of filler materials with guided tissue regeneration, use of nonporous hydroxyapatite blocks, transplanted natural third molars and custom-made bioabsorbable root analogs. This study aims to histologically describe OAC closure using an injectable alloplastic material Easy Graft Biphasic? as a technique for OAC closures. Nine (9) 6-month old 2 kg rabbits were used in the study. Both sinuses of a rabbit were used, one serving as the control and the other experimental. After extraction of the first 2 upper premolars, access into the sinus was performed, creating 5mm perforations. Control sites were left untreated, while experimental sites were packed with Easy Graft Biphasic?. Three (3) rabbits were sacrificed at 3,6 and 9 weeks post-surgery. OAC closure, as seen by oral mucosal and sinus epithelium healing was observed for both control and experimental sites. Granulation tissue formation, angiogenesis, fibroblastic activity and osteoblastic activity was also present for both. Bone formation was observed, though only slower, for experimental sites that in controls. Inflammation was marked for the alloplastic group, which may be due to the host's foreign body reaction to the synthetic material. The regeneration of the sinus epithelium, due to poor slide preparation, has been difficult to ascertain. However, in the presence of a stable clot, the sinus epithelium had regenerated in experimental sites at 6 weeks. Control sites could have closed at around the same time or earlier. The oral mucosa had closed in control sites earlier than in experimental sites. Inflammation seemed to be localized only within the extraction socket and not within the oral mucosa epithelium. Through this study, it was found that, given enough time for bone formation and resolution of inflammation, the use of the injectable alloplastic material can close OAC's.